Pembelajaran Interaktif Bahasa Arab Pada Siswa Kelas 4 di SDIT Tunas Mulia Wonosari - Anwar, Khaerul; Hani, Isyfi; Nurfadhilah, Nurfadhilah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This study aims to analyze how interactive methods are applied in Arabic language learning in grade IV SDIT Tunas Mulia Wonosari, and to identify its impact on student engagement and understanding. Data collection for this descriptive qualitative study was conducted through observation, in-depth interviews with teachers, students, and documentation. The results of the study indicate that interactive learning can increase students' enthusiasm and active participation in Arabic language learning, especially in arranging hijaiyah letters. In addition, interactive Arabic language learning helps students develop and improve their cognitive, psychomotor, and affective skills, as well as collaboration and communication skills. However, this study also found varying challenges in student ability levels and effective classroom management. This study concludes that interactive learning has great potential to improve the quality of learning to arrange Hijaiyah letters in elementary schools.